Role of miRNA in the Development of Non-Melanoma Skin Cancer (NMSC): A Systematic Review - Muhammad Zaid Imron; Willy Sandhika; Cleodylon Reinard Susanto; Lusiani Tjandra (Majalah Biomorfologi, 2026)
Background: Non-melanoma skin cancers (NMSC), comprising basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC), are the most common skin malignancies worldwide. MicroRNAs (miRNAs), small non-coding RNA molecules that regulate gene expression, have increasingly been recognized for their roles in the pathogenesis and progression of NMSC. Objective: To systematically review the role of miRNAs in the development and progression of NMSC, as well as their potential clinical utility. Materials and Methods: The authors performed a comprehensive literature search in ScienceDirect, PubMed, and Cochrane databases following PRISMA guidelines. The articles were selected using Rayyan.ai based on relevance to PICO. Screening and quality assessment was performed using predefined eligibility criteria. A total of 16 studies met the inclusion criteria. Extracted data included differentially expressed miRNAs, their regulatory pathways, and their potential roles. This study employed descriptive synthesis. p-values or effect sizes were reported as available in the included studies (n = 16). Results: Several miRNAs were consistently reported as dysregulated in NMSC. Upregulated miRNAs included miR-21 and miR-31, while miR-203 was frequently downregulated. These miRNAs affect key oncogenic pathways, leading to alterations in apoptosis, proliferation, and cell cycle regulation. Across the included studies, dysregulated miRNA expression demonstrated significant associations with tumor development, invasiveness, and potential diagnostic or prognostic value (p < 0.05 in multiple studies). Conclusion: MiRNAs play a crucial role in the molecular pathogenesis of NMSC and represent promising biomarkers as well as potential therapeutic targets. Modulating specific miRNAs may offer new avenues for early detection and improved treatment strategies.